Occurrence of fungal foliar diseases on selected mangrove species in oil-spilled areas in Taklong Island National Marine Reserve, Nueva Valencia, Guimaras, Philippines - Panaguiton, Diana Dalino (Miagao, Iloilo U.P. Visayas, 2013)
The Solar 1 oil spill off the coast of southern Guimaras in 2006 affected the mangroves within Taklong island and Tandog Island National Marine Reserve (TINMAR) in Nueva Valencia. This study aimed to determine the severity and incidence of fungal foliar diseases as an indicator of weakened state on selected mangrove species. Specifically, it aimed to 1.) Isolate, characterize and identify fungal species associated with foliar diseases of selected mangrove species; 2.) quantify the occurrence of fungi and 3.) evaluate disease incidence and severity on selected mangrove hosts. A total of 500 symptomatic leaves were randomly sampled from six oil-contaminated sites and uncontaminated site within the reserve in March 2012. Fungi were isolated, described and identified to the genus level only based on available keys and monographs. In general, disease incidence at oiled sites (68-79 percent) were significantly higher (p=.000) compared with un-oiled site (54 percent) but severity was not high. All species showed significantly higher incidence (p=.034) at oiled sites compared with un-oiled sites. A total of 25 morphospecies were collected of which only Hyphomycete 2 was the most frequently collected at 10.8 percent. Species consistently isolated from foliar lesions were Pestalotia sp., Spermatia, Fusicoccum sp., Phyllosticta sp., Hyphomycete 2 and Ascomycete sp. Results of this study showed that despite the widespread occurrence of fungal foliar disease among the oil-contaminated mangroves, severity was low. This might be attributed to their natural defenses againts such infections as well as of the improvement of the overall health of the mangroves towards recovery six years after the spill.
Thesis (Master of Science in Biology) -- Miagao, Iloilo : University of the Philippines Visayas, April 2013.
Keywords: Mangroves -- Fungal Foliar Diseases; Mangoves -- Oil Spill -- Guimaras